2014
DOI: 10.7763/ijbbb.2014.v4.304
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Genes Related to Arsenic Detoxification in Rice Roots Using Microarray Analysis

Abstract: Abstract-Arsenic(As) contamination in natural environment is a problem in many countries. Plants exposed to As show cytotoxic effects as inhibit cellular function, disrupt metabolism and reduce the yield. However, little is known about the molecular mechanisms of rice early expose to arsenate (AsV) at low concentration (10μM). Therefore, to better understand the molecular basis of rice cells, we performed a large-scale during analysis of the rice transcriptome within 24 hours challenged with AsV, one kind of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…With application of metal(loid)s in the present study, an activation of the antioxidant apparatus in pigeonpea as well as pea indicated that increased oxidative burst is not attributed to the regulation of only one enzyme, but rather to the complex upregulation of several ROSscavenging enzymes (SOD, CAT, POX). An increase in the activity of antioxidant enzymes can be attributed to the induced transcription of their genes, probably mediated by free radicals (Duquesnoy et al, 2010;Nguyen et al, 2014;Ovečka and Takáč, 2014). In the present study, antioxidative activities varied among different organs, which could be related to the amount of metal(loid)s that accumulated differentially in the analyzed organs, to a much higher extent in roots than in leaves.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…With application of metal(loid)s in the present study, an activation of the antioxidant apparatus in pigeonpea as well as pea indicated that increased oxidative burst is not attributed to the regulation of only one enzyme, but rather to the complex upregulation of several ROSscavenging enzymes (SOD, CAT, POX). An increase in the activity of antioxidant enzymes can be attributed to the induced transcription of their genes, probably mediated by free radicals (Duquesnoy et al, 2010;Nguyen et al, 2014;Ovečka and Takáč, 2014). In the present study, antioxidative activities varied among different organs, which could be related to the amount of metal(loid)s that accumulated differentially in the analyzed organs, to a much higher extent in roots than in leaves.…”
Section: Discussionmentioning
confidence: 48%
“…An increase in the activity of antioxidant enzymes can be attributed to the induced transcription of their genes, probably mediated by free radicals (Duquesnoy et al, 2010;Nguyen et al, 2014;Ovečka and Takáč, 2014). In the present study, antioxidative activities varied among different organs, which could be related to the amount of metal(loid)s that accumulated differentially in the analyzed organs, to a much higher extent in roots than in leaves.…”
Section: Discussionmentioning
confidence: 69%
“…The As treatment affected transcription-, signaling- and hormone-related proteins, all of which are involved in the direct and retrograde communication between the nucleus and the organelles; their modulation could well disturb the normal development of the fruit [ 10 , 53 ]. Proteins related to transport and cell metabolism, also essential for ripening, probably served as a means for the tissue to sequester As into non-essential cellular structures and to increase the concentration of antioxidants needed to maintain an appropriate cellular redox state [ 54 ]. Supplementation with Si had a marked influence over the abundance of proteins associated with transcription, signaling and hormone metabolism, as also noted in the interaction of tomato with its pathogen Ralstonia solanacearum [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Results showed that transgenic expression of both OsGrxs in A. thaliana was sufficient to increase plant tolerance to As. Earlier studies reported that expression of OsGrx_C7 and OsGrx_C2.1 was induced during As stress in rice in addition to defense and stress responsive genes, transporters, heat-shock proteins, metallothioneins, sulfate-metabolizing proteins ( Norton et al, 2008 ; Chakrabarty et al, 2009 ; Gautam et al, 2012 ; Nguyen et al, 2014 ). In this study, similar results were observed through RT-PCR analysis, upon AsIII and AsV exposure ( Figure 1 ) supporting the possible involvement of OsGrxs in As metabolism and transport.…”
Section: Discussionmentioning
confidence: 99%